Instrument und Immanenz. Zur Sprachphilosophie der deutschen Frühromantik - Andrzejewski, Bolesław (Studia Germanica Posnaniensia, 2018)
In his article the author discusses the philosophy of the early romanticism in Germany, conncentrating on the romantic conception of language and its reference to the universe. Two tendencies in the philosophy of that period can be distinguished: 1st Schelling's "philosophy of nature" and so called "philosophical natural science", 2nd so called "true romanticism" (Novalis, F. Schlegel and others). By the former language was considered an instrument for establishing the unity of the universe, e.g. by tracing common sources of words. The "true" romanticists disregarded the existing spoken language of men and concentrated on the language of nature. The human language was interpreted as a late stage in the evolution of the language of the universe, disadvantageous to nature itself.